Maturation-Dependent HIV-1 surface protein redistribution revealed by fluorescence nanoscopy - Chojnacki, Jakub; Staudt, Thorsten M.; Glass, Bärbel; Bingen, Pit; Engelhardt, Johann; Anders-Ößwein, Maria; Müller, Barbara; Hell, Stefan; Kräusslich, Hans-Georg (Science, 2012)
Human immunodeficiency virus type 1 (HIV-1) buds from the cell as an immature particle requiring subsequent proteolysis of the main structural polyprotein Gag for morphological maturation and infectivity. Visualization of the viral envelope (Env) glycoprotein distribution on the surface of individual HIV-1 particles with stimulated emission depletion (STED) superresolution fluorescence microscopy revealed maturation-induced clustering of Env proteins that depended on the Gag-interacting Env tail. Correlation of Env surface clustering with the viral entry efficiency revealed coupling between the viral interior and exterior: Rearrangements of the inner protein lattice facilitated the alteration of the virus surface in preparation for productive entry. We propose that Gag proteolysis-dependent clustering of the sparse Env trimers on the viral surface may be an essential aspect of HIV-1 maturation.Rearrangements of the interior structural lattice cluster a surface glycoprotein as the virus preps for cell entry.Rearrangements of the interior structural lattice cluster a surface glycoprotein as the virus preps for cell entry.
Gesehen am 17.07.2018